Problematika Penegakan Hukum Lingkungan Terhadap Degradasi Ekosistem Pascatambang di Sulawesi Tenggara - Andi Musakkir Musni; Cakra Andreas Situmeang; Mus Mubarak (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Post-mining ecosystem degradation in Southeast Sulawesi demonstrates the serious impact of mining activities on the environment, particularly in terms of soil damage, water pollution, and the loss of ecological function in post-mining areas. Despite existing regulations governing reclamation and post-mining obligations, environmental law enforcement still faces various obstacles, both institutionally and in terms of business compliance. This study aims to analyze the challenges of environmental law enforcement regarding post-mining ecosystem degradation in Southeast Sulawesi. The research questions are: the effectiveness of environmental law enforcement regarding post-mining ecosystem degradation and the factors that hinder its implementation. The research method used is empirical legal research using legislative and sociological approaches, through the collection of primary and secondary data. The results indicate that environmental law enforcement has not been optimal due to weak oversight, low compliance by mining companies with reclamation obligations, and limited administrative and criminal sanctions. Furthermore, there is a gap between legal norms and field practices, contributing to the continued deterioration of post-mining ecosystems. In conclusion, strengthening legal instruments, increasing oversight capacity, and consistent enforcement of sanctions are necessary for effective post-mining environmental protection.